Are China's Ethnic Minorities Less Likely to Move? - Björn Anders Gustafsson; Xiuna Yang (Institute for the Study of Labor (IZA), 2015)
This study uses China's Inter-Census Survey 2005 to analyse the extent migration behaviour among 14 large ethnic minority groups and the Han majority. Results show that the probability to migrate to all types of destinations varies by province of origin, decreases by age, and in most cases, by expected income at the origin. Furthermore the probability to migrate is found to typically increase by length of education and decrease for females by the number of children. In most cases investigated, a minority ethnicity reduces migration probabilities for people registered in rural China. This is particularly the case for persons belonging to the Uyghur and Tibetan ethnic groups, but also for the Mongolian, Bai, Yao and Tujia groups. In contrast, Korean and Hui have a higher probability of migration than the majority. For people with an urban hukou there are fewer examples that minority ethnicity affects probability to migrate.
Keywords: J15; J61; J7; P23; 330; China; ethnic minorities; Uighur; Tibetan; Korean; Hui